Agriculture and Climate Beyond 2015 A New Perspective on Future Land Use Patterns - Brouwer, Floor; McCarl, Bruce A. (Environment & Policy, 2006)
Interactions between agriculture, climate and patterns of land use are complex. Major changes in agriculture, and land use patterns are foreseen in the next couple of decades in response to shifts in climate, greenhouse gas management initiatives, population growth and other forces. The book explores key interactions between changes in agriculture, patterns of land use and efforts to reduce greenhouse emissions from agriculture. The volume is based on inter-disciplinary science and policy interactions, exploring the way land use may aid in addressing or be affected by the onset of climate change and alterations in food demand. Future forces shaping land use decisions are examined, and its sensitivity to climate change is highlighted. Patterns of land use and the agricultural role in climate change mitigation are explored. Also, policy and social responses to the new perspectives on future land use patterns are identified. The perspective of the book is beyond the year 2015.